The performance of nursing against the risk of postpartum depression (Research, Society and Development, 2022)
It is estimated that worldwide depression may become the leading cause of mortality in the world. During pregnancy, women are more emotionally vulnerable, with a potential risk of developing depression, and they need to be welcomed and cared for with greater attention by the health team, especially if they have a previous history of mental illness. This study aims to know the Brazilian scientific production related to nursing and postpartum depression, through a bibliographic research. Early detection of postpartum depression is essential, however, it was observed that nurses find it difficult to recognize clinical signs of the disease. The service seems fragmented and unresolved, which compromises meeting this demand. Among the most used strategies for the approach are the groups of pregnant women and the search for studies that contemplate the humanization of care. In this sense, health care lacks team training to improve diagnosis as early as possible, inserting a multidisciplinary team into care and safe public health policies and practices for patients and professionals.